Analisis Perbandingan Kinerja Teknik Modulasi BPSK dan QPSK Menggunakan Kanal Flat Slow Fading Pada Sistem CDMA - Fitri Amillia; Muhammad Erpan (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2015)
Code Division Multiple Access (CDMA) is one of the access technology used in communication systems and provide the radio interface solution that can accommodate a wide range of voice, data and multimedia with high speed. In this research, which represents a model simulation of CDMA communication system using BPSK and QPSK modulation techniques through a slow flat fading channels, then the model is simulated with Simullink Matlab 7.8.0. Test results CDMA system simulation BPSK and QPSK modulation techniques through a slow flat fading channels, such as the value of Bit Error Rate (BER) QPSK modulation technique produced better performance than BPSK modulation technique.